Development of I-Spring Learning Media on Thematic Learning to Increase Learning Outcome of Students in Class IV SD Negeri 101772 Tanjung Selama - Hakiki Annisa Batubara; Naeklan Simbolon (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
Learning media is a tool and/or learning resource in presenting material that can create learning experiences, stimulate students in the learning process and make learning more effective, efficient and fun. This study aims to determine the feasibility of i-Spring-based learning media in thematic learning in class IV SD Negeri 101772 Tanjung Selamat. This study uses a Research and Development (R&D) research model following the Thiagarajan procedure (4-D Model). The subjects used in this study were fourth grade students at SD Negeri 101772 Tanjung Selamat. Data analysis uses (1) Feasibility test of media and materials that have met the valid and feasible criteria with 90% material feasibility results and 88% learning media feasibility results, (2) Development trials obtained the results of teacher and student responses that were worth 89.86% which were obtained through teacher and student response questionnaires. based on this analysis, it can be concluded that the i-Spring-based learning media in thematic learning is feasible to use and can improve student learning outcomes.